Implementasi Keselamatan dan Kesehatan Kerja (K3) Pada Proyek Pemasangan Kubikel di Gardu Induk GIS 150 KV Glugur PT PLN (Persero) Medan - Luthfiansyah, Faiz Agung; Khairunisa, Puteriyani; Simatupang, Nabilah Aprilia Marwa; Amri, Nurul Fadia; Chaniago, Syalha Nabila; Nasution, Winda Irma Asti; Astuty, Delfriana Ayu (Yayasan Jompa Research and Development, 2025)
This study aims to analyze the implementation of Occupational Safety and Health (OHS) in preventing workplace accidents in the Cubicle Installation Project at the GIS Substation of PT PLN (Persero) Medan. This project carries a high level of risk due to the involvement of high-voltage electrical systems and complex construction work. The research method used was descriptive qualitative, with data collected through direct observation, interviews, and documentation with 16 respondents consisting of field workers, HSE officers, project managers, and PLN management. The results indicate that the implementation of OHS in this project has been running well and is in accordance with the provisions of Law No. 1 of 1970, Government Regulation No. 50 of 2012, Minister of Manpower Regulation No. 26 of 2014, and Minister of Manpower Regulation No. 5 of 2018. Workers have used complete and appropriate Personal Protective Equipment (PPE), followed safe work procedures (SOPs), and attended regular briefings before work. The work area is well-organized, has adequate lighting and ventilation, and is equipped with emergency facilities such as fire extinguishers and first aid kits. OHS monitoring and reporting are conducted routinely through PLN's CSMS system, while hazardous waste management and worker support facilities meet healthy work environment standards. A zero-accident safety culture is also reflected in the implementation of Job Safety Analysis (JSA), Work Permit, and Hazard Identification and Risk Control (IBPR) prior to work commencing. Overall, the implementation of OHS on this project is effective in preventing workplace accidents and supporting safe, efficient, and environmentally friendly operations.